1989
DOI: 10.1289/ehp.8981201
|View full text |Cite
|
Sign up to set email alerts
|

Results of a United States and Soviet Union joint project on nervous system effects of microwave radiation.

Abstract: During the course of a formal program of cooperation between the United States and the Soviet Union concerning the biological effects of physical factors in the environment, it was concluded that duplicate projects should be initiated with the general goal of determining the most sensitive and valid test procedures for evaluating the effects of microwave radiation on the central nervous system. This report details an initial step in this direction. Male rats of the Fischer 344 strain were exposed or sham expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The changes analyzed in this study for brain signals in different sleep-wake states are found in agreement with previous published reports. 10,12,23,33,50 However, from literature review, it is evident that the changes in EEG frequencies are highly dependent on the exposure frequency, time of exposure, and the modulation frequency. Thus, in these conditions, the findings of the present study for EEG power spectrum analysis are unique.…”
Section: Discussionmentioning
confidence: 99%
“…The changes analyzed in this study for brain signals in different sleep-wake states are found in agreement with previous published reports. 10,12,23,33,50 However, from literature review, it is evident that the changes in EEG frequencies are highly dependent on the exposure frequency, time of exposure, and the modulation frequency. Thus, in these conditions, the findings of the present study for EEG power spectrum analysis are unique.…”
Section: Discussionmentioning
confidence: 99%
“…Stricter regulations limiting professional exposures to EMF in the fSU than in the US have been partly based on such reports [89]. Admittedly, some results could not be reproduced [90][91][92]. Certain experiments have been doubtful, for example, irradiation of eggs in an incubator by a static MP resulted in increased embryonic mortality.…”
Section: Uhf Therapy In Head and Neck Areamentioning
confidence: 99%
“…In a second experiment of the same group, 16 Hz amplitude modulated microwave (4 GHz) increased EEG beta activity already at SAR 8.4 W/kg, [Thuroczy et al, 1994], but as this intensity is still above the thermal threshold, arousal effects cannot be excluded. In a joint project in the USA and the former Soviet Union, EEG power spectra were recorded in rats submitted to continuous 2.45 GHz microwaves for 7 h (whole body SAR 2.7 W/kg) [Mitchell et al, 1989]. Although both groups reported incidences of statistically significant effects, changes did not affect the same frequency bands and, therefore, were considered to be unreliable [Mitchell et al, 1989].…”
Section: Effects On Spontaneous and Evoked Electrical Activity In Vivomentioning
confidence: 99%
“…In a joint project in the USA and the former Soviet Union, EEG power spectra were recorded in rats submitted to continuous 2.45 GHz microwaves for 7 h (whole body SAR 2.7 W/kg) [Mitchell et al, 1989]. Although both groups reported incidences of statistically significant effects, changes did not affect the same frequency bands and, therefore, were considered to be unreliable [Mitchell et al, 1989]. These data suggest that in animal experiments EEG activity changes little as long as microwave exposure remains in the nonthermal range.…”
Section: Effects On Spontaneous and Evoked Electrical Activity In Vivomentioning
confidence: 99%